Publication Trends in Craniofacial Distraction: A Bibliometrical Analysis. Issue 1 (January 2017) - Hashmi, Asra; Schumaier, Adam; White, Shenita; Yi, Christina; Khan, Faraz A.; Hanba, Curtis J.; Al-Mufarrej, Faisal
Abstract : Purpose: The purpose of this study was to analyze the craniofacial distraction literature published over the last 50 years and to determine various trends in publications. Methods: A literature search was conducted in November and December 2015. The date search range was 1965 to 2015. Databases searched included Medline, Web of Science, Biosis, SciELO, Data Citation, and Zoologic Records. Data were collected on distraction type, author specialty, date of publication, country, state (if United States), number of citations, journal name, journal type, and Le Fort type (for midfacial distractions). Results: Total number of craniofacial distraction publications was 1729. Cranial distraction accounted for (11%), midfacial (11%), and mandibular (78%). Largest increase in publications was in the 1990s, with 48 publications from 1991 to 1995 rising to 261 publications from 1996 to 2000. Among the cranial distraction publications, Plastic and Reconstructive Surgery (PRS) (67%) were the most frequent authors but among the midfacial and mandibular distraction publications, Oral and Maxillofacial Surgery (OMFS) were the most frequent authors (68% and 64%, respectively). Total number of citations was 26, 281 with OMFS (50.4%) and PRS (37%) being cited most frequently. Oral and Maxillofacial Surgery was cited most for mandibular and midfacial distraction, and PRS was cited most for cranial distraction. Conclusion: Research on craniofacial distraction has significantly increased since the 1970s, with mandibular distraction accounting for the majority of this rise. Among specialties, OMFS and PRS account for the majority of the literature. The United States leads the publication. Authors tend to publish distraction literature in their corresponding journal specialty, with the exception of PRS who publishes most frequently in OMFS journals.